Penerapan Aplikasi KPSP melalui Pelatihan Kepada Guru Kober dan Guru TK - Neli Sunarni; Aulia Ridla Fauzi; Rosidah Solihah (LPPM STIKes Muhammadiyah Ciamis, 2023)
Introduction: The SDIDTK activities are part of a comprehensive and high-quality child development program, focusing on stimulation, early detection, and intervention of developmental deviations during the first five years of life and for preschool children aged 5-6 years, utilizing the Pre-Screening Development Questionnaire (KPSP). The KPSP is employed at the family/community level by trained Early Childhood Education (PAUD) educators and kindergarten teachers. The Midwifery D3 Study Program at STIKes Muhammadiyah Ciamis has launched a new breakthrough, an Android-based KPSP application developed as a result of research conducted by faculty members from the Midwifery D3 Study Program. Objective: The purpose of this service was providing a solution to the problem of effectively and efficiently utilizing developmental screening through an Android-based KPSP application, accompanied by an improvement in knowledge regarding developmental screening in infants and toddlers. Method: This public service was conducted by identification, formulation of service instrument, conducting a pre-test on developmental screening for playgroup and kindergarten teachers, followed by the provision of materials related to child developmental screening and training on the usage of the KPSP application. The activity concludes with a post-test on knowledge of child developmental screening and the direct utilization of the KPSP application by playgroup and kindergarten teachers. Result: There was an increase in knowledge to 100% after being given counseling related to child development screening and training on using the KPSP application which succeeded in making kindergarten and Kober teachers more effective and efficient. Conclusion: Counseling in order to increase the knowledge of Kindergarten teachers and Kober teachers about child development screening has succeeded in providing a significant increase in knowledge.